2006
DOI: 10.1007/s10540-006-9010-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a HMG-CoA Reductase Gene from Eucommia ulmoides Oliver

Abstract: The 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) catalyzes the conversion of HMG-CoA to mevalonate, which is the first committed step in the pathway for isoprenoid biosynthesis in plants. A full-length cDNA encoding HMGR (designated as EuHMGR, GenBank Accession No. AY796343) was isolated from Eucommia ulmoides by rapid amplification of cDNA ends (RACE). The full-length cDNA of EuHMGR comprises 2281 bp with a 1770-bp open reading frame (ORF) encoding a 590-amino-acid polypeptide with two trans-membrane domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
(23 reference statements)
8
24
0
4
Order By: Relevance
“…The tissue expression pattern showed that HMGR had strongly expressed differences, which suggested that HMGR might be a constitutively expressing gene. The similar results were reported by Jiang et al (2006). In addition, the expression pattern in different tissues suggested that this gene is expressed in a tissue-dependent manner in pigs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The tissue expression pattern showed that HMGR had strongly expressed differences, which suggested that HMGR might be a constitutively expressing gene. The similar results were reported by Jiang et al (2006). In addition, the expression pattern in different tissues suggested that this gene is expressed in a tissue-dependent manner in pigs.…”
Section: Discussionsupporting
confidence: 88%
“…The HMGR gene has been widely cloned in many species, i.e. the human HMG-CoA reductase gene has been localized to human chromosome 5q12 by in situ hybridization and contains 20 exons and 19 introns (Humphries et al, 1985;Luskey and Stevens, 1985), chicken (Sato et al, 2003), rat (Simonet and Ness, 1988;Sundaresan et al, 1989;Duckworth et al, 1991) and some plants (Ha et al, 2003;Jiang et al, 2006). Information regarding this gene in pigs, however, is limiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PgHMGR1 was expressed in different levels among the tested organs, the PgHMGR1 gene seems to be expressed constitutively throughout ginseng development, which was similar to the characterized homologs from Salvia miltiorrhiza (Liao et al, 2009) and Eucommia ulmoides (Jiang et al, 2006). Indeed, the heterologous expression of the two fulllength ginseng HMGRs in the Arabidopsis hmgr1-1 mutant background showed that only PgHMGR1 could complement the dwarf and sterile phenotypes of hmgr1-1 (Suzuki et al, 2004), which suggests that PgHMGR1 is a functional ortholog of AtHMGR1.…”
Section: Pghmgr1 Localized Into the Cytoplasmic Organelles And Its Gementioning
confidence: 74%
“…HMGR catalyzes the conversion of HMG-CoA into mevalonate (MVA) to yield a biologically active isoprenoid precursor, isopentenyl pyrophosphate (IPP) unit (Friesen & Rodwell, 2004;Jiang et al, 2006;Wang et al, 2007), which serves as the basis for the biosynthesis of molecules used in many metabolic processes such as steroid biosynthesis (Pitera, Paddon, Newman, & Keasling, 2007), terpenoid biosynthesis (Cheng et al, 2007) and carotenoid biosynthesis (Tada et al, 1990). The isolation and molecular characterization of plant HMGRs have been performed in both monocots and dicots such as Arabidopsis thaliana (Dudareva et al, 2005), rice (Ha, Lee, Kim, & Hwang, 2001), Camptotheca acuminate (Maldonado-Mendoza, Vincent, & Nessler, 1997), Ganoderma lucidum (Shang et al, 2008), and hazel .…”
Section: Introductionmentioning
confidence: 99%